Three new species of bright-spored myxomycetes from Asia and the second world record of Perichaena maculosa - Vlasenko, Anastasia V.; Enkhtuya, Ochirbat; Degidmaa, Turmunkh; Enkhjargal, Enkhtaivan; Chelobanov, Boris P.; Vlasenko, Vyacheslav A. (Phytotaxa, 2024)
Three new species of myxomycetes are described in the genera Arcyria, Metatrichia and Tubifera. Each species is given a full description, along with details of ecology and distribution. They are compared to morphologically similar species, using both light and scanning electron microscopy. DNA extracted from the 18S nrDNA regions (SSU), confirmed the three new species.